Effect of zinc and iron fertilization on growth, yield and nutrient uptake of mustard (Brassica juncea L.) in loamy sand soil (Journal of Oilseed Brassica, 2025)
A field experiment was conducted during rabi season 2021-22 at Sardarkrushinagar, Gujarat in loamy sand soil. Total eight treatments were tested in randomized block design with four replications. Mustard variety GDM 4 was sown at a distance of 45 cm x 15 cm. Various growth parameters viz. plant height and number of branches/plant, yield attributing characters and seed yield (2324 kg/ha) and stover yield (5381 kg/ha) were recorded significantly maximum with the application of RDF+ 4.0 kg ZnSO4 /ha and 7.5 kg FeSO4 /ha soil application at basal + 0.5% ZnSO4 and 0.5% FeSO4 foliar spray at 30 and 45 DAS (T8 ). While, number of siliquae per plant was found significantly higher in application of RDF+ 8.0 kg ZnSO4 /ha and 15.0 kg FeSO4 /ha soil application at basal. Application of RDF+ 4.0 kg ZnSO4 /ha and 7.5 kg FeSO4 /ha soil application at basal + 0.5% ZnSO4 and 0.5% FeSO4 foliar spray at 30 and 45 DAS (T8 ) recorded significantly higher nutrients uptake of nitrogen, phosphorus, potash, sulphur, zinc and iron by mustard crop.